Mutation in Bmpr1b Leads to Optic Disc Coloboma and Ventral Retinal Gliosis in Mice - Yan, Xiaohe; Atorf, Jenny; Ramos, David; Thiele, Frank; Weber, Susanne; Dalke, Claudia; Sun, Minxuan; Puk, Oliver; Michel, Dian; Fuchs, Helmut; Klaften, Matthias; Przemeck, Gerhard K. H.; et al. (Investigative Ophthalmology & Visual Science, 2020)
PURPOSE. The clinical phenotype of retinal gliosis occurs in different forms; here, we characterize one novel genetic feature, (i.e., signaling via BMP-receptor 1b).
CRIS-Team WoS Importer:2020-03-20